Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF): análise da distribuição dos recursos entre 1999 e 2009 - Fernandes, Fernanda Ferreira (2011)
This work studies the distribution of resources by the National Program for the Development of the Familiar Agriculture (PRONAF) between 1999 and 2009, which is a credit program, that positions itself as a public policy to extinguish the difficulties of access to resources by familiar farmers. The aim of this work is to investigate if, regardless of the changes in its legislation to increase the incorporation of the poorest familiar farmers in poorer regions, the program has had a logic of distribution concentrated in the most dynamic familiar farmers and developed regions. This study has as background the post-Keynesian theoretical perspective, in which banks, as economic agents, are the main responsible for the supply of credit, that is essential to the economic development. In the view of Keynes, banks take into account their expectations about the borrower‟ future ability of payment, the alternative forms of return on assets and their desire for security. The prospect is that these economic agents prefer to direct resources to the most dynamic agents, which can provide greater guarantees, in most economically developed spaces, to the less risky sectors of the economy. The trend, from this, is of concentration of the credit. The case of the rural sector is more problematic because of the higher risk associated with the activities performed in it. Hence it comes the hypothesis of the work: that the PRONAF could present difficulties in the distribution of resources to the poorest familiar farmers, especially in poorer regions. We performed the study of the PRONAF‟s distribution from 1999. Both the analysis of the total distribution for Brazil and for each region indicated, considering the whole period, a relative improvement of the distribution between 2003 and 2006 and a worsening in the distribution from then on. In addition to this analysis, we set up capitation indicators from the PRONAF by municipality and we associate them with Rural Development Indicators, by the statistical technique Correspondence Analysis in order to observe the profiles of familiar farmers and spaces that have received the resources. We made associations for three periods between 2001 and 2009. The results showed that, in general, the final position of the less developed municipalities was worse than the initial position, except in the Northeast region. Furthermore, we note, in general, that the most integrated familiar farmers groups (D and E) have improved their participation in detriment of the poorest familiar farmers groups (A, A/C, B and C). Finally, we associate the participation of the group B with the volume released by the Program Bolsa Família (between 2004 and 2006 and 2007 and 2009), in the Northeast region. The results showed an inverse relationship between the level of rural development and the level of receipt of the Program, showing that the Bolsa Família is able to reach more intensely the poorer municipalities. Furthermore, the association between the participation of the group B and the volume released by the Bolsa Família also presented an inverse relationship. In our view, it is not the poorest familiar farmers‟ difficulty that explains the low relative access, but the difficulties imposed on them by the bank logic.